Diagnostic Challenges: A Review of Non Classic Thyroid Function Test Patterns - Pooja Varadaraj; Renuka Panchagnula (National Journal of Laboratory Medicine)
Disorders of thyroid function are common. Aside from some obvious presenting features of thyroid disease, such as goitre, which can easily be identified, patients with thyroid conditions may present with non specific symptoms. Therefore, a high index of clinical suspicion is required, and confirmation of diagnosis usually depends on accurate measurement and interpretation of Thyroid Function Tests (TFTs). In most cases, the results of TFTs are straightforward and present a familiar pattern of hypo or hyperthyroidism that is easy to recognise. However, sometimes they can seem confusing. These are the discordant or non classic TFT reports. The extent of literature available on TFTs is enormous. The difficulty that arises when encountering a discordant TFT report lies in sifting through the vast amount of literature. A discordant TFT report implies situations where the thyroid hormone and Thyroid Stimulating Hormone (TSH) values do not fit into the pattern of either classic primary or secondary hypo or hyperthyroidism. The present article thus serves as a ready reckoner for those discordant TFT patterns. The way the present article may be utilised is as follows: when a TFT report appears discordant, the TFT pattern may be noted down. Then, the conditions in which the pattern may be seen could be searched in the present article. Next, by correlating with the clinical history, the best fit may be found among the conditions. If a reasonable explanation is not possible, we might need to look for any assay interference. Through a few case examples provided toward the end of the article, this process of deduction has been made evident. The deduction method moves from the more common to the less common causes for the unusual patterns of TFT. Interpretation of a discordant TFT report may be done by first considering a few common causes, such as pregnancy, Non Thyroidal Illness (NTI), and drug usage. Additionally, repeating the TFTs after a few weeks sometimes brings back the classic TFT pattern and helps us identify the factor that was leading to the discordant values. If neither of these conditions fits, assay interference or the less common causes for discrepant values might be considered and worked upon. These are the aspects that have been covered here to enable a successful interpretation of any TFT report.